PHYSICAL EDUCATION BY DISTANCE LEARNING TECHNOLOGIES AS A FACTOR OF STUDENTS' HEALTHY LIFESTYLE - Grebinka, Galina; Zubritsky, Yaroslav; Rozhko, Elena; Taranenko, Maxim (Mountain School of Ukrainian Carpaty, 2021)
The article consider the issue of a healthy lifestyle of students in the process of their physical education while studying in higher education institutions. The urgency of the study due to significant problems in maintaining the health of young people on a national scale, due to the introduction of quarantine restrictions in educational institutions. The purpose of the study is to identify the possibilities of the discipline "Physical Education" by means of remote technologies in free economic education in the formation of skills of a healthy lifestyle of students. Based on the study, the use of a set of general scientific theoretical methods: analysis, synthesis, systematization, generalization. It is established that the implementation of the current educational process provides a priority before physical education – the preservation and change of pupils and students in the formation of their healthy lifestyle skills. The practice of using distance learning technologies in physical education of students is studied, the possibilities of such educational process in formation of motivations and needs of students in observance of the basic healthy ways of life in the conditions of quarantine are analyzed. It is determined that the latter should be reviewed: classes based on a personality-oriented approach, the availability of these recommendations for the formation of motivations for physical activity; providing opportunities for students to monitor indicators of individual development; acquisition of skills to increase valeological culture of nutrition; increase of motor activity in the modes of the school day and maintenance of the sanitary and hygienic mode. According to the results of the study, information on potential innovative distance technologies has been expanded to optimize the impact of physical education on the student's personality in order to educate users of a healthy lifestyle during student years, which will ensure their future health.